The Significance of Cytokine Content and Substance P In the Diagnostics And Treatment Of Chronic Salpingoophoritis With Chronic Pelvic Pain Syndrome - Ziyaeva E.R (Genius Publishing Group, 2024)
Chronic salpingoophoritis (CSO) is rightfully considered the most common pathology in practical gynecology, its frequency reaches 60-65%. CSR in 24-30% of cases causes the development of chronic pelvic pain syndrome. The presence of CPPS often causes pathology in both the physical and mental spheres, which leads to maladaptation in marriage, and, accordingly, an increase in divorces, frequent temporary or even permanent loss of ability to work, which makes it a medical and social problem. CSО complicated with CPPS is an urgent problem in gynecology. We decided to study the pathogenetic factors of CSО and CPPS based on changes in cytokines and substance P(SP).
Keywords: Chronic salpingoophoritis; chronic pelvic pain syndrome; cytokines; substance P